The Relationship of Multiset, Stirling Number, Bell Number, and Catalan Number - Wamiliana; Attiya Yuliana; Fitriani (Science and Technology Indonesia, 2023)
Catalan numbers is not as famous as Fibonacci numbers, however this number has own its beauty and arts. Catalan numbers was discovered by Ming Antu in 1730, however, this numbers is credited to Eugene Catalan when he was studying parentheses in 1838. Catalan numbers mostly occurs in counting or enumeration problems. The Catalan numbers can be defined in more than one forms, and the most famous form is Cn = 1/n+1(2nn). In this study we will discuss the multiset construction and the relationship of the results of Multiset with Stirling, Bell, and Catalan numbers.